EVALUASI KINERJA RANTAI PASOK MENGGUNAKAN SCOR (SUPPLY CHAIN OPERATIONS REFERENCE) 11.0 - Bimbing Dipongga Agamis (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Intense business competition makes every company formulate a new strategy to take a leading position in the competition. Business competition lies in how a company can apply the process of creating products and services that are cheaper, higher quality and faster with other business competitors. Therefore, a thorough evaluation and measurement of all aspects related to the company's performance is required. Evaluation of supply chain performance at CV. XYZ uses the Supply Chain Operations Reference (SCOR 11.0) model. Activities that determine industrial strategies based on the attributes of Reliability, Responsivenes, Cost and Assets which are then measured using a level 1 matrix, because the measurement of process performance standards uses a level 1 matrix. With calculations carried out using the SCOR 11.0 model at CV. XYZ in 2019, the results obtained from POF (perfect order fullfilment) of 89,33%, OFCT (order fullfilment cycle time) 20-21 days, COGS (cash of good sold) of 67,62%, SCMC (supply chain management cost) of 67,30%.